2015
DOI: 10.1111/jicd.12175
|View full text |Cite
|
Sign up to set email alerts
|

Association of Porphyromonas gingivalis with high levels of stress‐induced hormone cortisol in chronic periodontitis patients

Abstract: This research offers support for the association between P. gingivalis and higher levels of cortisol in chronic periodontitis patients. These results suggest that high levels of cortisol could increase the occurrence of P. gingivalis in the biofilm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…In particular, P. gingivalis has the ability to change the composition of plaque and the inflammatory milieu through one of the virulence factors of P. gingivalis, gingipains, which converts complement C5 to C5a, thereby inducing inflammation and also modulating the Toll-like receptor response, thus preventing leukocytes from being efficient killers [72]. Studies have shown a positive association between cortisol levels and the presence of P. gingivalis in subgingival plaques of localized periodontitis, after adjusting for age, sex, income, and smoking status [73]. P. gingivalis alters the host immune response, thereby contributing to dysbiosis of the periodontal microbiome and magnifying its capacity to produce periodontitis [74].…”
Section: Stress and Periodontitis: The Biofilm Connectionmentioning
confidence: 99%
“…In particular, P. gingivalis has the ability to change the composition of plaque and the inflammatory milieu through one of the virulence factors of P. gingivalis, gingipains, which converts complement C5 to C5a, thereby inducing inflammation and also modulating the Toll-like receptor response, thus preventing leukocytes from being efficient killers [72]. Studies have shown a positive association between cortisol levels and the presence of P. gingivalis in subgingival plaques of localized periodontitis, after adjusting for age, sex, income, and smoking status [73]. P. gingivalis alters the host immune response, thereby contributing to dysbiosis of the periodontal microbiome and magnifying its capacity to produce periodontitis [74].…”
Section: Stress and Periodontitis: The Biofilm Connectionmentioning
confidence: 99%
“…Studies[ 7 8 ] have found that cortisol in saliva (1) represents “free” biologically active cortisol, (2) is unaffected by salivary flow rate, (3) consistently and reliably reflects free serum cortisol and HPA axis reactivity, and (4) is also a more practical assessment tool than venipuncture in stress research due to its potential to elicit spurious increases in cortisol secretion reflecting a “hyperstress” component. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Objective are favored with the increase in oxygen metabolism in the periodontal tissues. 40,41 The methods of measurement of salivary and serum cortisol are used for the diagnostic categorization of chronic stress. Both methods are characterized as viable to obtain parameters that configure the stress.…”
mentioning
confidence: 99%